2000
DOI: 10.1248/cpb.48.559
|View full text |Cite
|
Sign up to set email alerts
|

Butyrolactones from Aspergillus terreus.

Abstract: In the process development of lovastatin using Aspergillus terreus DRCC 152 in solid state fermentation, we have isolated a new butyrolactone-IV (3) along with the previously reported butyrolactone-I (1) and butyrolactone-II (2) produced under submerged conditions. The structure of compound 3 has been characterized as 3-hydroxy-5-[2-(1-hydroxy-1-methylethyl)-2(R)-2,3-dihydro-benzo[b]furan- 5 ylmethyl]-4-(4-hydroxyphenyl)-5-methoxycarbonyl-(5R)-2,5-dihydro-2 -furanone on the basis of spectroscopic studies. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
97
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(101 citation statements)
references
References 0 publications
4
97
0
Order By: Relevance
“…1) Some different types of metabolites have been subsequently isolated from A. terreus strains. [2][3][4][5][6][7][8] Among these, some sesquiterpene lactone and butyrolactone compounds have exhibited potent acetylcholinesterase inhibition activity and cyclin-dependent kinases inhibition activity. 4,7) In our continuing search for new anti-tumor compounds from marine fungi, A. terreus was isolated from mangrove-associated marine sediments collected in Guangxi Zhuang Autonomous Region of China.…”
mentioning
confidence: 99%
“…1) Some different types of metabolites have been subsequently isolated from A. terreus strains. [2][3][4][5][6][7][8] Among these, some sesquiterpene lactone and butyrolactone compounds have exhibited potent acetylcholinesterase inhibition activity and cyclin-dependent kinases inhibition activity. 4,7) In our continuing search for new anti-tumor compounds from marine fungi, A. terreus was isolated from mangrove-associated marine sediments collected in Guangxi Zhuang Autonomous Region of China.…”
mentioning
confidence: 99%
“…An extract from Aspergillus terreus BCC 4651 exhibited moderate activity against Mycobacterium tuberculosis H37Ra (minimum inhibitory concentration (MIC) 25 mg/ml) and the 1 H-NMR spectrum of the extract showed a unique profile, therefore, we selected the strain for large scale fermentation and chemical investigation. This study led to the isolation of two new butenolides, butyrolactones VI (1) and VII (2), together with the known compounds, butylolactone I (3), 1) butyrolactone II (4), 2) butyrolactone IV (5), 3) butyrolactone V (6), 4) and aspernolide B (7). 5) A known diketopiperazine, bisdethiodi(methylthio)-acetylaranotin (8), [6][7][8] was also isolated as an antimycobacterial constituent of the culture extract.…”
mentioning
confidence: 99%
“…Because of the structural similarity of furandiones 1 and 2 with butenolides such as butyrolactone I-IV, 15,16) aspernolides A and B, 17) which were also isolated form A. terreus, the biosynthetic pathway for the two furandiones was probably similar with those of butenolides. The reported feeding experiments on the biosynthesis of xenofuranones A and B 18) and butyrolactone I 19) have shown that these butenolide derivatives were produced via condensation of α-ketocarboxylic acids such as phenylpyruvic acid and p-hydroxyphenylpyruvic acid.…”
Section: Resultsmentioning
confidence: 99%